Big Things - Little Things - Pretzer, D.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study examined the economic effects of applying controllable management factors for farrow-to-finish operations. Average producers in Kansas market 7 pigs/litter with an average feed conversion of 4.58. Improvement in 9 areas of management increased profits on 240 litters by $43,680. Each item appears small. However "Big Things" come from the sum of "Little Things".
Keywords: Swine; Management factors; Farrow-to-finish operations